3g+4(-6g+3g)=1-g

Simple and best practice solution for 3g+4(-6g+3g)=1-g equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3g+4(-6g+3g)=1-g equation:


Simplifying
3g + 4(-6g + 3g) = 1 + -1g

Combine like terms: -6g + 3g = -3g
3g + 4(-3g) = 1 + -1g

Remove parenthesis around (-3g)
3g + 4 * -3g = 1 + -1g

Multiply 4 * -3
3g + -12g = 1 + -1g

Combine like terms: 3g + -12g = -9g
-9g = 1 + -1g

Solving
-9g = 1 + -1g

Solving for variable 'g'.

Move all terms containing g to the left, all other terms to the right.

Add 'g' to each side of the equation.
-9g + g = 1 + -1g + g

Combine like terms: -9g + g = -8g
-8g = 1 + -1g + g

Combine like terms: -1g + g = 0
-8g = 1 + 0
-8g = 1

Divide each side by '-8'.
g = -0.125

Simplifying
g = -0.125

See similar equations:

| 3(4C-1)-16=10C+3 | | .25(4x+10)=8 | | 18+5T=-3N-12 | | 8y-8=35-7y | | 3y+4+10y-17=14-23y+16-7y | | -5N+10=-3N-12 | | 6y+7-19=7y+13-3y-21 | | A(x-1)-bx=0 | | 8X+58=8X+14 | | -10z+75=-5 | | 2x-10i=8-(4iy) | | 4-C=25 | | 8X+8=5X+7 | | 9*x*x*x+6*x*x=0 | | 15+4y=y | | 125-3x=24+23x | | 2x-10i=8-(4y)I | | 27-18=3(X-3) | | 12-8x=123-43x | | -127-8x=-68-10x | | 28+3Y-6=13Y-13-3Y | | 5x+3=27-4x | | 6x+21=5x-51 | | x+19+3x=-15-3x-22 | | 114-6x=9+24 | | 5x+2y-3x+4y= | | 4x+34=5x+1 | | 8x^3-8x^2+x=4x^2-5x+1 | | 3x-7=7x-17 | | 18.23=x+0.21*x | | 7x+13=97-6x | | 75-5x=8x+18 |

Equations solver categories